'A Great Number of … Women'?: The Changing Involvement of Female Workers in Master and Servant Cases in England, 1685–1860. Issue 1 (1st September 2020) - Chartrand, Madeleine
Abstract : Between the late seventeenth and mid-nineteenth centuries in England, female workers' involvement in employment disputes that were summarily adjudicated by Justices of the Peace (magistrates) under master and servant law decreased. Women's diminishing work opportunities in arable agriculture after the late eighteenth century likely contributed to this downward trend. However, female textile workers were a notable exception, as manufacturers and magistrates used employment law to coerce greater productivity from them. Master and servant prosecutions both reflected changes in women's occupational patterns and served as a means to exploit a feminized textile labour force that was crucial to industrialization and to our interpretation of its nature and causes.